Occupational Therapy for People Living With Human T-Lymphotropic Virus 1: Importance and Effectiveness of an Intervention Plan at the Level of Prevention and Rehabilitation - Sampaio, Edilson Coelho; Aben-Athar, Cintia Yolette Urbano Pauxis; Pinto, Denise da Silva; Vallinoto, Antonio Carlos Rosário; Cayres Vallinoto, Izaura Maria Vieira (Frontiers in Medicine, 2022)
Introduction: Human T-lymphotropic virus 1 (HTLV-1)-associated myelopathy (HAM) restricts activities of daily living (ADLs), affecting health and quality of life. Occupational therapy is used to promote independence during ADL in people living with HTLV (PLHTLV). Objective: To quantify the clinical aspects, levels of functionality, performance in ADLs and occupational roles of PLHTLV and propose an occupational therapeutic intervention. Method: A cross-sectional, descriptive, observational study was designed with 40 PLHTLV monitored at two referral laboratories of the Federal University of Pará. The Evandro Chagas Research Institute Neurological Disability Scale (EIPEC-2), the Barthel Index and the Occupational Roles Identification List were applied. The G test and Fisher’s exact test (to identify associations between qualitative variables), the Mann–Whitney test (to identify associations between quantitative variables) and Pearson correlation analysis (to identify associations between the total Barthel Index and EIPEC-2 scores) were performed with Microsoft Excel and BioEstat 5.0, and the significance level was set at p ≤ 0.05. Results: Motor aspects, the presence of spasticity, sensory aspects and pain in the lumbar region and lower limbs were significantly (p=0.0002) higher among symptomatic individuals, who also had more difficulties urinating, traveling up and down stairs and transferring from a chair to a bed. Being a worker, performing housework and socializing (with friends or family members) were the most affected activities among HAM patients. Conclusion: The impact of HAM on PLHTLV should include an intervention plan with occupational therapists in rehabilitation programs to create an important third-level prevention initiative, which may help achieve short-, medium- and long-term goals. Asymptomatic PLHTLV should also be able to prevent future ADL impairment.